Relationship Between Muscle Dysmorphia and other Factors with Supplement Consumption Among Selected Gym Members in Jakarta - Mohammad Rafid Billy Ramadhan; Anna Fitriani (Faculty of Public Health Universitas Indonesia, 2023)
Ergogenic supplements can enhance exercise performance. However, many gym members use them without consulting professionals such as nutritionists/dietitians, increasing the risk of adverse effects. This study investigates the consumption of ergogenic supplements and factors associated with them among members of selected fitness centers in Jakarta. This cross-sectional study was conducted on 116 participants from 3 fitness centers in Jakarta. The independent variables studied were Muscle Dysmorphia, Exercise Addiction, self-esteem, body image, age, gender, exercise duration, exercise experience, exercise intensity, and social media exposure. Data was collected via interviews based on a prepared questionnaire. Results showed that 67.2% of the respondents had used ergogenic supplements, with the majority using whey protein for muscle enhancement reasons. The main sources of information were friends (39.7%) and the internet (37.2%). The chi-square test showed a significant relationship between male gender (OR = 3.055; 95%CI: 1.298—7.188), exercise experience of 7—12 months (OR = 5.4; 95%CI: 1.621—17.991), and >1 year (OR = 5.091; 95%CI: 1.910—13.571) with supplement consumption. In conclusion, this study unveils a high prevalence of ergogenic supplement consumption, particularly whey protein for muscle enhancement, among fitness center members.